2022
DOI: 10.1002/tcr.202100295
|View full text |Cite
|
Sign up to set email alerts
|

′Ab Ovo′ Chiral Phases and Chiral Reagents for Liquid Chromatographic Separation and Isolation of Enantiomers

Abstract: The de-novo approach of mixing chirally pure reagents or Cu(II)-L-amino acid complexes in the slurry of silica gel for preparing TLC plates was reported from author's laboratory and was successful for separation and isolation of enantiomers. Using high molar absorptivity molecules, e. g., 1,5-difluoro-2,4-dinitrobenzene and cyanuric chloride, more than 38 new chiral derivatizing reagents were synthesized in our laboratory by straightforward nucleophilic substitution with simple chiral auxiliaries. Besides, (S)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
0
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 167 publications
0
0
0
Order By: Relevance
“…Ibuprofen was the first chiral drug of the NSAIDs class to be switched to the single-enantiomer version in 1994, then the ketoprofen (31) was submitted to chiral switching and marketed as the (S)-(+)-enantiomer in 1998. In this case, the metabolic enantiomerization from (R) to (S) in vivo, and vice versa, was shown to be negligible in humans [26]. Other chiral NSAIDs are naproxene, carprofen, fenoprofen, flurbiprofen, and indoprofen, and for all of them, the (S)-enantiomer is the eutomer.…”
Section: Non-steroidal Anti-inflammatory Drugs (Nsaids)mentioning
confidence: 87%
See 1 more Smart Citation
“…Ibuprofen was the first chiral drug of the NSAIDs class to be switched to the single-enantiomer version in 1994, then the ketoprofen (31) was submitted to chiral switching and marketed as the (S)-(+)-enantiomer in 1998. In this case, the metabolic enantiomerization from (R) to (S) in vivo, and vice versa, was shown to be negligible in humans [26]. Other chiral NSAIDs are naproxene, carprofen, fenoprofen, flurbiprofen, and indoprofen, and for all of them, the (S)-enantiomer is the eutomer.…”
Section: Non-steroidal Anti-inflammatory Drugs (Nsaids)mentioning
confidence: 87%
“…Moreover, chiral metal-organic frameworks (CMOF) materials are commonly used for chiral recognition, separation, and catalysis [25]. More new methods for isolation of enantiomers and control of their enantiomeric purity have been proposed [26,27]; however, given the high cost of enantioselective syntheses [28,29] or the separation of enantiomers [30,31], the racemic mixtures of chiral drugs are still often used in therapy. It has also to be considered that the determination of the exact 3D structure of drug candidates is of foremost importance for the pharmaceutical industry in different stages of the discovery [32].…”
Section: Introductionmentioning
confidence: 99%
“…In 1998, ketoprofen underwent chiral conversion and was released as the S(+)‐enantiomer. In this instance, it was demonstrated that there is very little metabolic enantiomerization in humans from (R) to (S) and vice versa [85]. Ibuprofen acts as a nonselective inhibitor of COX, affecting both COX‐1 and COX‐2 activities.…”
Section: Therapeutic Efficacy Of Chiral Molecule In the Treatment Of ...mentioning
confidence: 99%